N6‐methyladenosine Steers RNA Metabolism and Regulation in Cancer. Issue 7 (6th May 2021) - Dong, Shenghua; Wu, Yutong; Liu, Yadi; Weng, Hengyou; Huang, Huilin
Abstract: As one of the most studied ribonucleic acid (RNA) modifications in eukaryotes, N 6 ‐methyladenosine (m 6 A) has been shown to play a predominant role in controlling gene expression and influence physiological and pathological processes such as oncogenesis and tumor progression. Writer and eraser proteins, acting opposite to deposit and remove m 6 A epigenetic marks, respectively, shape the cellular m 6 A landscape, while reader proteins preferentially recognize m 6 A modifications and mediate fate decision of the methylated RNAs, including RNA synthesis, splicing, exportation, translation, and stability. Therefore, RNA metabolism in cells is greatly influenced by these three classes of m 6 A regulators. Aberrant expression of m 6 A regulators has been widely reported in various types of cancer, leading to cancer initiation, progression, and drug resistance. The close links between m 6 A and cancer shed light on the potential use of m 6 A methylation and its regulators as prognostic biomarkers and drug targets for cancer therapy. Given the notable effects of m 6 A in reversing chemoresistance and enhancing immune therapy, it is a promising target for combined therapy. Herein, we summarize the recent discoveries on m 6 A and its regulators, emphasizing their influences on RNA metabolism, their dysregulation and impacts in diverse malignancies, and discuss the clinical implications of m 6 A modification in cancer. Abstract : As one of the best studied ribonucleic acid (RNA) modifications in eukaryotes, N 6 ‐methyladenosine (m 6 A) plays a predominant role in controlling gene expression and further influences physiological and pathological processes, including oncogenesis and tumor progression. Here we review the functions of m 6 A and its regulators in RNA metabolism control, their oncogenic or tumor suppressive roles in diverse malignancies, as well as the application of m 6 A methylation in cancer diagnosis and therapeutics.